2011
DOI: 10.1177/1087057110396371
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Establishment of G-Protein-Coupled Receptor–Expressing Cell Lines by Site-Specific Integration

Abstract: IntroductIon The conventional drug development process is expensive and time-consuming, and despite large investments in research and development activities, the success rate of bringing a new drug to the market is low. the most prominent target class is that of g-protein-coupled receptors (gpcrs), which cover about 60%-70% of recently developed drugs. 1 upon modulation by extracellular ligands, these cell surface receptors mediate the transduction of extracellular stimuli into intracellular signals. the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Nehlsen et al (2009) also reported antibody gene integration into CHO cells using Flp-RMCE. Recently, site-specific integration into a target locus was applied for the evaluation of packaging cell lines producing retroviral vectors with high and predictable titer (Gama-Norton et al 2010) and for the establishment of recombinant G-proteincoupled receptor-expressing cell lines (Schucht et al 2011). In these studies, however, a transgene cassette was introduced into the genome only once.…”
Section: Discussionmentioning
confidence: 99%
“…Nehlsen et al (2009) also reported antibody gene integration into CHO cells using Flp-RMCE. Recently, site-specific integration into a target locus was applied for the evaluation of packaging cell lines producing retroviral vectors with high and predictable titer (Gama-Norton et al 2010) and for the establishment of recombinant G-proteincoupled receptor-expressing cell lines (Schucht et al 2011). In these studies, however, a transgene cassette was introduced into the genome only once.…”
Section: Discussionmentioning
confidence: 99%
“…Schucht and coworkers [84] used high expressing master cell lines to express G protein-coupled receptors (GPCRs). Wilke et al used RMCE in mutant CHO Lec3.2.8.1 cells to produce glycoproteins with the well-established glycosylation pattern in a homogenous form [93].…”
Section: Recombinant Protein Expressionmentioning
confidence: 99%
“…Once having tagged and expressing a hotspot with recombination target sites, integration of any transgene of interest can be achieved in a short time. Since screening is not required anymore, the cell line development is significantly speeded up [84,85].…”
Section: Recombinant Protein Expressionmentioning
confidence: 99%
“…The main advantage of this system is that the recombinant cell lines have a single copy of the transgene at a genome site known to be transcriptionally active. Recently, RMCE was employed for the overexpression of several different antibodies [51] and GPCRs [52] from clonal CHO cell lines. RMCE can also be used stable cell pool generation following co-transfection and selection of the tagged host cells [50].…”
Section: Targeted Transgene Integrationmentioning
confidence: 99%